A review of oral surgery-related papers published in the British Journal of Oral and Maxillofacial Surgery during 2011 and 2012. Issue 2 (February 2015) - Tahim, A.S.; Goodson, A.M.C.; Payne, K.F.B.; Brennan, P.A.
Abstract This paper is a synopsis of all articles relating to oral surgery that were published in the British Journal of Oral and Maxillofacial Surgery (BJOMS) between January 2011 and December 2012. Of the 57 published, 40 (70%) were full-length articles that predominantly focused on implantology, dentoalveolar surgery, and bisphosphonate osteonecrosis of the jaws (BONJs). In addition, a number of short communications, technical notes, and letters to the editor described rare cases, unusual complications, and novel surgical techniques.